Eighteenth-century genomes show that mixed infections were common at time of peak tuberculosis in Europe - Kay, Gemma L.; Sergeant, Martin J.; Zhou, Zhemin; Chan, Jacqueline Z.-M.; Millard, Andrew; Quick, Joshua; Szikossy, Ildikó; Pap, Ildikó; Spigelman, Mark; Loman, Nicholas J.; Achtman, Mark; Donoghue, Helen D.; et al. (Nature communications, 2015)
Tuberculosis (TB) was once a major killer in Europe, but it is unclear how the strains and patterns of infection at ‘peak TB’ relate to what we see today. Here we describe 14 genome sequences of M. tuberculosis , representing 12 distinct genotypes, obtained from human remains from eighteenth-century Hungary using metagenomics. All our historic genotypes belong to M. tuberculosis Lineage 4. Bayesian phylogenetic dating, based on samples with well-documented dates, places the most recent common ancestor of this lineage in the late Roman period. We find that most bodies yielded more than one M. tuberculosis genotype and we document an intimate epidemiological link between infections in two long-dead individuals. Our results suggest that metagenomic approaches usefully inform detection and characterization of historical and contemporary infections. Tuberculosis was once a major killer in Europe. Here the authors use metagenomics to obtain genomic sequences of Mycobacterium tuberculosis from human remains from eighteenth-century Hungary, revealing mixed infections within individuals as well as presence of the same strain in two individuals.